ДИНАМІКА КІЛЬКІСНОГО СКЛАДУ КУПЕЦТВА ПІВДЕННОЇ УКРАЇНИ У ПЕРШІЙ ЧВЕРТІ ХІХ СТОЛІТТЯ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of social and economic development of the Southern Ukraine in the first quarter of the XIX th century. The paper deals with dynamics of the quantitative changes among the merchants of the Southern Ukraine. An attempt to consider causes of these changes is done. The paper is concerned with the role of the Russian government tax policy in the processes of alterations in the number of the merchants.